A Framework to Select the Best Strategy for Iran's Entry into the Repair and Maintenance Market of Oil Drilling Rigs - Pantea Motamed; Javad Majrouhi (Salehan Institute of Higher Education, 2018)
The oil and gas service industry revenue is projected to rise to 350 billion in 2020, and a major part of such services belong to repair and maintenance (R&M) of the drilling rigs. Therefore, with regard to the number of jack-up rigs in Iran and the Persian Gulf, the R&M and improvement of these types of rigs become particularly important, especially due to the high lifespan of these rigs, which increases the time frequency of basic repairs. Nevertheless, Iran is suffering from lack of management and knowledge in the field of project resource management in this industry. Therefore, knowing the strategies and effective criteria for this industry is essential. In this paper, 15 criteria affecting the selection of R&M strategy were determined through interviews with experts, and the effect of each criterion on each alternative (seven strategies) was studied, and the most appropriate R&M strategy was then selected through analytic hierarchy process (AHP). The results show that the best strategy for Iran's entry into the R&M market is to perform all basic repairs of the rig, followed by license and joint venture. Finally, the best strategy was applied at R&M of Sina1 rig, comparing the results with those for Iranian rigs such as Modarres and Rajaei, the repairs of which were carried out in foreign yards, indicates the low cost of domestic repairs and the economic justification.